The Energy Amplifier, an "Ecological" Reactor - Eleftheriadis, Christos A. (HNPS Advances in Nuclear Physics, 2019)
The main ideas for the Energy Amplifier (EA) are presented, as they have been developed at CERN [1]. The discussion concerns with the safety and environmental features of this new kind of reactor which are far more better than the ones of the conventional reactors. A comparison is also given with fusion reactors and other non-nuclear methods for energy production, such as coal burning.